Exploring the Potential of Circular Economy in Ukrainian Enterprises - Завадських, Ганна Миколаївна; Zavadskykh, Hanna; Safonik, N.; Moroz, E.; Alekseieva, K.; Honcharenko, I. (The Grassroots Institute, 2025)
EN: The circular economy concept promotes sustainable development and more sustainable production of products. The dissemination of relevant ideas is linked to the challenges of rational resource use, waste losses, climate change, and environmental protection. The aim of the article is to conduct an analytical study of the practice and prospects of implementing measures by manufacturing enterprises within the circular economy framework in Ukraine. Using a case study approach, the research examines how Ukrainian manufacturing enterprises are transitioning to a circular economy. The Centre for Resource Efficient and Cleaner Production (RECP) database was used to analyze the cases. The results show that the activities of the RECP Centre under the EU Environment Programme have positively impacted the implementation of resource efficiency measures at Ukrainian manufacturing enterprises. Companies' investments in the replacement, modernization, automation, and installation of new equipment vary considerably depending on their capabilities, bringing economic and environmental benefits. The paper identifies the stimulating and discouraging factors of macro- and microlevel influence on the prospects for introducing the circular economy in Ukraine. The practical significance of the work lies in the quantitative assessment of investments, savings, and environmental effects (reduction of energy, water, gas consumption, and waste reduction) from the measures taken by manufacturing enterprises to rationally use resources.
Keywords: Circular economy; Closed-loop economy; Circular production; Sustainable development; Rational use of resources; Energy efficiency